Enrichment strategy with Cereus jamacaru DC. in a clearing area introduced by vegetative propagation (Research, Society and Development, 2021)
Mandacaru (Cereus jamacaru DC) is an endemic species of the caatinga that is endangered due to anthropic action through the practice of extractive agriculture, deforestation, fires, among others. The research aimed to evaluate the survival and development rates of Cereus jamacaru DC. introduced by vegetative propagation in clearing areas in the semi-arid region of Paraíba. 223 cladodes were planted in three clearings in the Experimental Space Reserved for Studies of Ecology and Dynamics of the Caatinga - Area II, arranged in lines spaced 1m between plants and 2m between lines. Cladodes size and diameter were measured and monthly monitoring of reproductive survival and phenophases was correlated with precipitation data for the period from January to July 2017. There was no mortality in the first months after planting, but only from the month of May, when the peak was registered with 33 individuals, with mortality still being observed in the month of July, when the death of nine individuals was registered, making up a percentage of 18.8% of the total implanted cladodes. In general, C. jamacaru proved to be viable for planting in a clearing area, and could become an alternative crop for farmers on their properties, serving in the recovery of degraded areas.